Whole Body Vibration Training - Chanou Κωνσταντίνα; Gerodimos Βασίλης; Κaratrantou Νάντια; Zisi Βασιλική; Tziamourtas Αθανάσιος; Tsiokanos Αθανάσιος; Kriki Θεοδώρα (Inquiries in Physical Education and Sport, 2009)
The aim of this study was to review the effects of whole-body vibration training on the physical performance of healthy subjects, as well as the possible mechanisms responsible for those effects. Exploration of the long-term effects of whole-body vibration revealed an increase of the isometric and dynamic knee extensor strength, as well as of the vertical jump of the vibration group. The literature regarding vibration effects on the flexibility, the hormonal and skeletal system as well as balance is limited, thus, safe conclusions referring to adaptations cannot yet be drawn. It seems, however, that the age, the program duration and the vibration characteristics may significantly affect balance and bone density. The results regarding the acute effects of whole-body vibration on strength are controversial, with studies reporting increase or decrease or no effect on the dynamic knee extensor strength. No conclusions can be drawn when exploring the hormonal system; it seems, though, that interval training can affect the secretion of hormones such as testosterone, growth hormone and cortisol. The vertical jump is improved after a few bouts of vibration training, improvements which are not maintained after the program completion. Furthermore, although balance and flexibility seem to improve, the current literature is rather poor, therefore, more research is required. Finally, vibration seems to increase the heart rate, relatively less, however, compared to other exercise types like the stationary cycling. Despite the large number of studies conveyed on vibration training, no valuable conclusions can yet be made, therefore, further research is necessary.